Integrasi Nilai-nilai Islam dalam Pembelajaran PAI Berbasis Teknologi Digital: Sebuah Kajian Pustaka - Ilham, Seprian (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the integration of digital technology and Islamic values in Islamic Religious Education (PAI) based on Sinta-accredited publications from 2025. Using a library research approach, five relevant articles were reviewed to identify trends, strategies, and challenges in integrating technology with religious values in PAI learning. The findings indicate that digital tools such as interactive modules, Learning Management Systems (LMS), videos, and gamification effectively enhance student engagement, understanding, and internalization of Islamic values. The success of integration largely depends on the teacher’s digital literacy and pedagogical competence. Effective strategies include project-based learning, interactive digital activities, and reflection exercises to strengthen students’ character and spirituality. However, some studies reveal gaps, such as limited analysis of long-term impact on students’ religious practices and lack of explicit technology designs emphasizing Islamic values. This review provides theoretical insights for developing PAI learning models that balance technological innovation with value-based education, serving as a reference for teachers and curriculum developers in the digital era.